الولادات الميتة وكفاءة استخدام الشبكات العصبية الاصطناعية في التنبؤ بمعدلاتها أنموذج العراق - هاشم كزار الطائي ا.د لطيف; محمد امين م.د. زينب (Journal of College of Education, 2021)
The subject of the dead births is one of the topics that has not received enough amount of study. Most of the researchers have not took in their consideration the geographical aspect. They only dealt with the medical side only. They didn’t have any idea concerning the geographic distribution from one place to another. The definition of the child dead mean he was born without any sign that he was alive, since the week of 24 of the pregnancy or after may be the child was died during labor or delivery research of Geographical distribution dead birth in Iraq. From the period of (2007 to 2014) which made the possibility of predicting of dead birth coming from (2014 to 2020) it also gives the prediction of the rate of dead births per (2007 to 2014) and by using the neural and industrial networks we can compare the results to arrive the best prediction which is the man aim of science to control of the phenomenon under study.